PERBEDAAN HASIL BELAJAR KELAS REGULER DAN EKSTENSI DALAM MATA KULIAH PENYUNTINGAN DI UNIVERSITAS INDRAPRASTA PGRI TAHUN AJARAN 2015/2016 - Samosir, Astuti (Lentera: Jurnal Ilmiah Kependidikan, 2016)
This research aimed to describe the comparison between learning result in regular class and extention class in the course subject penyuntingan at Universitas Indraprasta PGRI in academic year 2015/2016. The population of this research was the fifth semester students with numbered Â± 250 students and the sample were 120 students. The data was collected by using test. The conclusion of this research are as follows: (1) The highest score was came from Reguler B class with the mean score 89,23, the second highest score was came from Ekstensi A class with the mean score 87,1, while the mean scores of Reguler A and Ekstensi B class were similar, that is 85,33. (2) The result of hypothesis testing is as follows: (a) the t-test in Reguler A and Ekstensi A is tcount = 1,77 and ttable = 1,67, it means that H1 is accepted. (b) the t-test in Reguler A and Ekstensi B class is tcount = 0 and ttable = 1,67, it means that H1 is rejected, (c) the t-test in Reguler B and Ekstensi A class is ttest = 1,68 and ttable = 1,67, (d) the t-test in Reguler B and Ekstensi B is tcount = 3,10 and ttable = 1,67, it means that H1 is accepted.